ADVERTISING AND ITS TYPES (COMPARING THE GERMAN AND UZBEK LANGUAGES) - Yigitalieva Zilola Muratovna; Iminova Gulshod Alisher kizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article is devoted to the study of advertising text. Various approaches to the classification and definition of the main and secondary components are considered and systematized.